PREDICTIVE VOLATILITY MODELS ON JKSE AND FIVE STOCK INDEX FROM DEVELOPED COUNTRIES - Nawatmi, Sri; Santosa, Agus Budi; Maskur, Ali; Sudiyatno, Bambang (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The global economy in 2021-2022 tends to slow down due to the Covid-19 pandemic, followed by the Russian invasion of Ukraine, which further weakens global economic conditions. This study aims to determine alternative predictive models for the JKSE and five developed country stock price indices (Singapore's FTSE, China's SSEC, Japan's Nikkei225, England's FTSE, and America's DowJones) during a time of slowing world economy (January 2021 – September 2022). The results of the study show that the JKSE shows lower volatility than the other five developed countries with a stock price index that tends to increase. The stock price indices for the five developed countries have high volatility and tend to decrease for China and Japan, while the stock price indices for Singapore, England and America tend to increase. An alternative predictive volatility model for JKSE stock returns is GARCH (1.1), Singapore's FTSE is ARCH (1), China's SSEC is ARCH (1), Japan's Nikkei 225 is GARCH (1.2) while the UK's FTSE100 and America's DowJones are EGARCH (1,1). These results indicate that FTSE and DowJones stock returns have a leverage effect where good news causes less volatility than bad news. When there is volatility in stock returns, especially FTSE100 and DowJones, business risk increases. This can cause stock investors to move their funds to countries with low investment risk